Analysis of Early Childhood Stimulation Training Program through the Detection of Child Growth and Development Activities on the Ability of School Cadres - Modjo, Dewi; Sudirman, Andi Akifa (International Journal Papier Public Review, 2020)
Stimulation is an activity to stimulate the basic abilities of children aged 0-6 years so that the child grows and develops optimally. Every child needs to receive regular stimulation as early as possible and continuously at every opportunity. This study aims to determine the analysis of the Stimulation Training Program for children through the Detection of Child's growth and development on the ability of school cadres to stimulate early childhood growth and development. This research method is a quantitative study using a quasi-experimental design. The type of sampling is two-stage random sampling. The sample of this research is school cadres of Early Childhood Education (PAUD) consisting of 16 Schools for Playgroups (KB), 32 Schools of Right-Kindergarten (TK), and 2 Schools of Child Care (TPA) in the Limboto Health Center Work Area. The results showed that there was a significant and significant effect of development detection training on the ability of school cadres to simulate child growth. The ability of school cadres to stimulate children's growth and development has increased knowledge before and after training. There is a significant and significant effect of developmental detection training on the ability of school cadres to stimulate child development. It is necessary to empower cadres evenly and periodically by related parties (the Health Office and Pusekesmas) in order to improve the growth and development screening skills carried out by school cadres. It is also hoped that this will improve the child's health status so that the child can grow and develop properly.